Lighthouse : an illuminating history of the world's coastal sentinels - Grant, R. G. (2018)
"Lighthouse captures the romance of these isolated, life-saving towers in words and contemporary images, along with the inventiveness and incredible feats of engineering it took to create them. This stunning visual exploration features 100 of the most innovative and beautiful lighthouses built during seafaring's golden age, from 1700-1900"--Back cover.
Prologue: The saga of the Eddystone light -- Wonders of the world : a brief history of the lighthouse -- Defying the elements : the perilous business of lighthouse building -- A light in the darkness : the evolution of lights and lenses -- Keepers of the light : splendors and miseries of the lighthouse crews -- Epilogue: The end of an era.
Keywords: Lighthouses -- History; Lighthouses -- Design and construction -- History; ARCHITECTURE -- Buildings -- Landmarks & Monuments; HISTORY -- Oceania; TRAVEL -- Pictorials; Lighthouses; Lighthouses -- Design and construction; History; History